Beyond Static and Singular Community: Diverse Participation of the Baduy Community in Tourism - Elfrida, Tuti (ASEAN Journal on Hospitality and Tourism, 2025)
This study examines the diverse forms of tourism participation within the Baduy community in Indonesia, challenging monolithic portrayals of indigenous peoples as either wholly resistant or fully accepting of tourism. Drawing on qualitative fieldwork and thematic analysis, the research reveals a spectrum of responses, ranging from non-participation and cautious engagement to proactive involvement, shaped by a range of interrelated factors. These include spatial proximity to visitor routes, generational positioning, spiritual orientation, motivation, gender roles, and networks. The findings suggest that participation is not a fixed category but a dynamic and fluid process, where individuals and groups shift their level and mode of engagement depending on context, opportunity, and alignment with adat. Rather than viewing tourism solely as a threat to cultural integrity or an economic opportunity, many Baduy community members exercise agency by filtering tourism through adat-based priorities. Participation thus becomes a strategic and selective act, employed for adaptation, cultural expression, or local benefit, while refusal to participate equally reflects autonomous decision-making. By highlighting this internal diversity, the study contributes to broader debates on indigenous tourism, emphasizing the importance of moving beyond simplistic binaries. It calls for a more nuanced understanding of indigenous participation that foregrounds community-defined interests and values.